2022
DOI: 10.3390/jcdd9050133
|View full text |Cite
|
Sign up to set email alerts
|

β-Caryophyllene Ameliorates Cyclophosphamide Induced Cardiac Injury: The Association of TLR4/NFκB and Nrf2/HO1/NQO1 Pathways

Abstract: Background: β-caryophyllene (BCP), a natural sesquiterpene, is extensively present in the essential oils of several plants. Cyclophosphamide (CYC) is an anticancer drug. However, its clinical usage is inadequate due to its cardiotoxicity. The aim of this study was to study the effects of BCP on cardiac injury induced by CYC exposure, and to identify the underlying mechanism of action. Methods: Five groups of Wistar rats were allocated. Group I (Normal), II (BCP), and III (CYC) acted as controls. Group IV, V (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Herein, BCP amplified the antioxidant status and mitigated oxidative damage in the DCM mouse heart, evidenced by a reduced level of MDA and increased level of GSH. In agreement, BCP showed to attenuate cyclophosphamide and doxorubicin-mediated myocardial injury via repressing lipid peroxidation and amelioration of the endogenous antioxidant system. Moreover, the antioxidant potential and free radical scavenging activity of BCP might be linked to the noticed alleviation of oxidative injury in DCM mice .…”
Section: Discussionsupporting
confidence: 54%
“…Herein, BCP amplified the antioxidant status and mitigated oxidative damage in the DCM mouse heart, evidenced by a reduced level of MDA and increased level of GSH. In agreement, BCP showed to attenuate cyclophosphamide and doxorubicin-mediated myocardial injury via repressing lipid peroxidation and amelioration of the endogenous antioxidant system. Moreover, the antioxidant potential and free radical scavenging activity of BCP might be linked to the noticed alleviation of oxidative injury in DCM mice .…”
Section: Discussionsupporting
confidence: 54%
“…β-Caryophyllene: β-Caryophyllene is a terpenoid found in many herbs and spices, including black pepper, oregano, and cloves. Studies have shown that β-caryophyllene can shield the cardiac tissues against cardiotoxicity by mitigating inflammation, reducing collagen deposition, and improving cardiac function in rat models [151].…”
mentioning
confidence: 99%
“…Bioactive against cardiac fibrosis (Figures were adopted and modified from ACS, MDPI, Sigma, and Pepdraw).β-CaryophylleneTerpenoids many herbs and spices, including black pepper, oregano, and cloves[151] Apple, grape, tomato, green tea, broccoli, pine, and ginkgo leaf. [138] Apigenin Flavonoids J. Cardiovasc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these metabolic alterations were attenuated in rats receiving doxycycline. Similarly, the study by Nancy S. Younis demonstrated the cardioprotective effects of β-caryophyllene, a natural sesquiterpene found in the essential oils of several plants, on cardiac injury induced by cyclophosphamide exposure, in 30 male Wistar rats (group 1: normal, group 2: β-caryophyllene, group 3: cyclophosphamide, group 4: β-caryophyllene + cyclophosphamide (100 mg/kg), group 5: β-caryophyllene + cyclophosphamide (200 mg/kg)) [ 12 ]. β-caryophyllene administration was associated with activated Nrf2/HO1/NQO1 and inhibited TLR4/NFkB pathways with ensuing antioxidative action and diminished inflammatory and apoptosis responses.…”
mentioning
confidence: 99%